2014
DOI: 10.1002/jsfa.6977
|View full text |Cite
|
Sign up to set email alerts
|

Changes in olive oil volatile organic compounds induced by water status and light environment in canopies of Olea europaea L. trees

Abstract: This is the first report on qualitative changes in VOCs induced by light environment and/or water status. This information is valuable to better understand the role of environmental factors on the sensory quality of virgin olive oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…Previous studies on the effect of either the light environment or the water status on VOO quality did not consider what happened when both factors were changed concomitantly. In a recent study, we showed that the interaction between irrigation, canopy position and year significantly affected the development of fruit colour change (and thus the progression of maturation) and the concentration of many volatile compounds in VOOs . In the present study, we confirmed the individual effects of tree water status and light exposure, although we did not find any evidence of significant interactions between those factors on spectrophotometric indices, fatty acid composition, phenolic composition and concentration of VOOs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous studies on the effect of either the light environment or the water status on VOO quality did not consider what happened when both factors were changed concomitantly. In a recent study, we showed that the interaction between irrigation, canopy position and year significantly affected the development of fruit colour change (and thus the progression of maturation) and the concentration of many volatile compounds in VOOs . In the present study, we confirmed the individual effects of tree water status and light exposure, although we did not find any evidence of significant interactions between those factors on spectrophotometric indices, fatty acid composition, phenolic composition and concentration of VOOs.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 25 and 50 g of N, P 2 O 5 and K 2 O per tree were supplied to all trees in 2008 and 2009, respectively. The trees had started fruit production in 2005 (approximately 5 kg per tree) and had reached full production by the time the experiments were started …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations